Reduction of Energy Use for Heating in Detached Houses using Passive Technics - Kalmár, Ferenc; Kalmár, Tünde (International Journal of Engineering and Management Sciences, 2022)
Reduction of energy use in buildings continue to be one of the most important goals in this sector. The aim of our research was to analyse the effects on the heating energy demand of passive technics. In the case of a detached house the energy savings using mass wall, Trombe-Michel wall and sunspace was determined. The calculations have been performed in the case of a building with average thermophysical characteristics and in the case of a building having similar geometry but its external building elements fulfilling the requirements of nearly zero energy buildings. It was proven, that some of the mentioned technics may lead to higher energy demand for heating, so a complex energy analysis has to be carried out before implementing them.